Penerapan Hukum Adat di Indonesia dalam Penyelesaian Perkara Pidana pada Kasus Pencurian Sepatu di Aceh - Putri, Meisya Assyifa; Nareswari, Naura; Adawiah, Helmy Robiatul; Gulshan, Nadia; Anargya, Audri Razan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Custom norms that develop in society in traditions and customs passed down from generation to generation are the customary law. In contrast to positive law, which is based on accepted social norms and covers topics such as property ownership, inheritance, and marriage, negative law is based on facts. Discussion of traditional customs and values is the core of this system, that customary law has an impact on the social and economic life of the community that practices the law. In general, Customary Law is customary law, meaning that its provisions are based on the will of the community and can change over time, becoming non-written law that is recognized by communities everywhere. This nation also recognizes Adat as a valid form of law. When Indonesia became a nation, one of the things created and contained in the 1945 Constitution was the supremacy of law. As written in article 18B paragraph 2 of the 1945 Constitution, “which explains that Indonesia as a country recognizes and respects the unity of customary law communities and their traditional rights as long as they are still alive and in accordance with the development of society and also the principles of the Republic of Indonesia or the Unitary State of the Republic of Indonesia, as stated in regulated in law.” This law can also be said to be one of the oldest laws when compared to other legal systems in Indonesia because it has been passed down from generation to generation by the people.